Efek Sistem Pengendalian Internal Terhadap Penerimaan Retribusi Alat Pemadam Api Ringan - Haryanti, Febby; Hendarsyah, Decky (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
This research aims to show the effect of the internal control system on the receipt of retribution for light fire extinguishers at the Bengkalis Regency Fire Department. This research was built using descriptive quantitative methods. The population of this research is all personnel who work at the Bengkalis Regency Fire Department. The sampling technique used purposive sampling, with the criteria that personnel who were in direct contact with the receipt of retribution for light fire extinguishers and obtained a total sample of 27 people. Sources of data using primary data and secondary data, in the form of questionnaires and literature study. The data were analyzed using simple linear regression before being tested for validity, reliability, and normality. This research found that the internal control system had a positive and significant effect on the acceptance of retribution for light fire extinguishers at the Bengkalis Regency Fire Department. This research can contribute to the Bengkalis District Fire Service Office by increasing the acceptance of retribution for light fire extinguishers to impact Bengkalis Regency regional income positively.